2018
DOI: 10.1007/s13300-018-0510-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Insulin Infusion Characteristics in Type 1 Diabetes Children and Adolescents in Qatar

Abstract: AimTo describe continuous subcutaneous insulin infusion (CSII) characteristics in type 1 diabetes mellitus (T1DM) children and adolescents using a standardized protocol in routine clinical settings in Qatar.MethodsA total of 138 T1DM patients (62 males; 76 females; mean age 9.8 ± 3.4 years) with a mean diabetes duration of 2.4 ± 1.9 years initiated CSII (MiniMed® Veo®™ and MiniMed® 640 G insulin pumps; Medtronic, Northridge, CA, USA) in 2016 and 2017. CSII characteristics and glycated hemoglobin (HbA1c) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This open-label, non-randomized, single-arm, single-center, clinical investigation study was conducted at Sidra Medicine in Doha, Qatar, and enrolled individuals aged 7-18 years with type 1 diabetes > 1 year, on MDI with SMBG, with or without RT-CGM or isCGM, with no prior pump experience, and with an HbA1c level < 12.5%. Individuals were recruited at regular clinic visits, following the clinical pathway for therapy [21]. This clinical assessment emphasizes the following individual aspects: frequency of SMBG controls per day, knowledge of carbohydrate counting, insulin dose adjustments based on carbohydrate intake and blood glucose level, the ability to identify changes in insulin requirements due to physical activity and sick days, ability to recognize, troubleshoot and manage hyperglycemia and hypoglycemia.…”
Section: Methodsmentioning
confidence: 99%
“…This open-label, non-randomized, single-arm, single-center, clinical investigation study was conducted at Sidra Medicine in Doha, Qatar, and enrolled individuals aged 7-18 years with type 1 diabetes > 1 year, on MDI with SMBG, with or without RT-CGM or isCGM, with no prior pump experience, and with an HbA1c level < 12.5%. Individuals were recruited at regular clinic visits, following the clinical pathway for therapy [21]. This clinical assessment emphasizes the following individual aspects: frequency of SMBG controls per day, knowledge of carbohydrate counting, insulin dose adjustments based on carbohydrate intake and blood glucose level, the ability to identify changes in insulin requirements due to physical activity and sick days, ability to recognize, troubleshoot and manage hyperglycemia and hypoglycemia.…”
Section: Methodsmentioning
confidence: 99%
“…4,20 The results from previous studies comparing MDI versus CSII are conflicting. 4,[21][22][23][24][25] In some literature, it has been shown that CSII is superior to MDI in lowering hemoglobin A1c levels as well improving glycemic profile. 21,23 However, others showed no difference between the 2 groups especially in the first year of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4,[21][22][23][24][25] In some literature, it has been shown that CSII is superior to MDI in lowering hemoglobin A1c levels as well improving glycemic profile. 21,23 However, others showed no difference between the 2 groups especially in the first year of treatment. 4,25 Also, there was no significant difference between CSII and MDI regarding non-severe hypoglycemia as an adverse effect in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a study from Qatar, CSII significantly improved glucose control in T1DM children and adolescents who use a standardized protocol. A reduction of HbA1c by 1.6% was achieved after 1 year of CSII initiation (95). A report from Qatar was the first to demonstrate the use of the hybrid closed-loop system in managing a patient with T1DM that resulted in a 1.3% decrease in HBA1c value.…”
Section: Resultsmentioning
confidence: 99%